PEMBERDAYAAN KEWIRAUSAHAAN KARANG TARUNA DI KAWASAN BANTARAN SUNGAI BENGAWAN SOLO, LAMONGAN - Desrina Yusi Irawati; Nany Suryawati; Lucia Ina Trisjanti (LPPM UNIVERSITAS HASYIM ASY'ARI TEBUIRENG JOMBANG, 2021)
Pesanggrahan Village is a village located on the banks of the Bengawan Solo River, Laren District, Lamongan Regency. In Pesanggrahan Village, there are youth groups, but they have not carried out entrepreneurial activities. Even though one of the goals of the youth organization is to develop an entrepreneurial spirit. This is because members of the youth organization are passive, the management and members are less skilled in starting a business, and lack of funds. Therefore, community service is carried out in the form of providing entrepreneurship knowledge through counseling, discussions to choose the type of business, and starting a simple business. The counseling contains material on entrepreneurial motivation, the benefits of entrepreneurship, home-based entrepreneurship, preparation for opening a business, determining profit, and healthy business space. The business that is being developed by the youth organization is a coffee shop business. The realization of a coffee shop business is carried out by preparing a business place and procuring coffee shop facilities. The result of mentoring youth organizations in pioneering coffee shops is to increase the motivation of young people to become entrepreneurs, open jobs, increase cash for youth organizations, and add supporting facilities in the village sports room.